Threatened Biodiversity and Traditional Ecological Knowledge: Associated Beliefs, Customs and Uses of Herpetofauna among the `Are`Are on Malaita Island, Solomon Islands - Pollard, Edgar Maeniuta; Thaman, Randy; Brodie, Gilianne; Morrison, Clare (Ethnobiology Letters, 2015)
Biodiversity and traditional ecological knowledge (TEK) are in danger of being lost in many societies, especially in the rapidly urbanising Pacific Islands. Herpetofauna, in particular, are globally threatened along with their associated cultural knowledge and beliefs. The aim of this study was to examine the species richness and conservation status of herpetofauna and associated TEK among the `Are`Are on Malaita Island, Solomon Islands. Questionnaire surveys were used to collect and gather information from local informants separated into equal sex and age cohorts. A total of 18 different species of frogs and lizards were recorded and described with seven distinct cultural uses identified. Informants above the age of 60 exhibited greater herpetofaunal knowledge with males slightly more informed than females. Our results clearly show that action must be taken to document and preserve community TEK in the Solomon Islands as a foundational basis for both biodiversity and cultural conservation.